2016
DOI: 10.1371/journal.pone.0153677
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-Induced Calcium Shifts in Chick Retinal Glial Cells

Abstract: Neuroglia interactions are essential for the nervous system and in the retina Müller cells interact with most of the neurons in a symbiotic manner. Glutathione (GSH) is a low-molecular weight compound that undertakes major antioxidant roles in neurons and glia, however, whether this compound could act as a signaling molecule in neurons and/or glia is currently unknown. Here we used embryonic avian retina to obtain mixed retinal cells or purified Müller glia cells in culture to evaluate calcium shifts induced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…In addition, MGCs synthesize glutathione, a molecule involved in the reduction in reactive oxygen species (ROS). Recently, it was described that glutathione also activates calcium‐mediated signalling (Freitas et al., ). MGCs achieve hydroelectrolytic balance of retinal tissue through the regulation of the extracellular ion concentration and pH, thereby avoiding neuronal swelling in hypoosmotic stress. For this purpose, MGCs display ion channels, aquaporins and purinergic transporters, which facilitate water uptake and ion transport (Vogler et al., ). MGCs actively participate in the recycling of photopigments from photoreceptors, catalysing the conversion of all‐ trans ‐retinal in 11‐ cis ‐retinol by retinaldehyde‐binding protein.…”
Section: Mgcs In Healthmentioning
confidence: 99%
“…In addition, MGCs synthesize glutathione, a molecule involved in the reduction in reactive oxygen species (ROS). Recently, it was described that glutathione also activates calcium‐mediated signalling (Freitas et al., ). MGCs achieve hydroelectrolytic balance of retinal tissue through the regulation of the extracellular ion concentration and pH, thereby avoiding neuronal swelling in hypoosmotic stress. For this purpose, MGCs display ion channels, aquaporins and purinergic transporters, which facilitate water uptake and ion transport (Vogler et al., ). MGCs actively participate in the recycling of photopigments from photoreceptors, catalysing the conversion of all‐ trans ‐retinal in 11‐ cis ‐retinol by retinaldehyde‐binding protein.…”
Section: Mgcs In Healthmentioning
confidence: 99%
“…Despite the flourishing literature on antioxidant systems in the retinal environment, our group was the first to examine the signaling role of GSH on both M€ uller glia and retinal neurons from the vertebrate (avian) eye. 18 Initial characterization of the [Ca 2C ]i dynamics showed that, while cultured neurons selectively respond to KCl (labeled as b III tubulin positive cells), large Ca 2C inwards were observed in GSH-stimulated M€ uller cells (labeled and identified as 2M6 positive cells). We have also observed that GSH selectively evokes abundant [Ca 2C ]i variations in M€ uller cells at the milimolar range, and that purified retinal neurons do not respond to GSH in a broad concentration gradient (10 mM -10 mM).…”
Section: Glutathione In Retinal M€ Uller Gliamentioning
confidence: 99%
“…[ 3 H] GABA release induced by GSH was also observed in cultured M€ uller cells or in dense mixed neuron-glia cultures, but not in purified neuronal cells. 18 GSH might be interacting at the P2X 7 receptor, as the effect was blocked by BBG or A74003. Addition of BAPTA-AM, a calcium chelator, also blocked propidium iodine uptake induced by GSH (or ATP) in M€ uller glial cells.…”
Section: Gsh Induces [Ca 2c ]I Transients and Gaba Release Through Glmentioning
confidence: 99%
See 2 more Smart Citations